THE EFFECT OF ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) DISCLOSURE AND DIVIDEND POLICY ON FIRM VALUE (Empirical Study on Companies Listed in the SRI KEHATI Index of the Indonesia Stock Exchange for the Period 2019-2022) - Kusnadi, Carissa Alliyah Nareswari; Hadiprajitno, Paulus Theodorus Basuki (Diponegoro Journal of Accounting, 2024)
The aim of this research is to analyze the influence of Environmental, Social, and Governance (ESG) disclosure and dividend policy on firm value. The population in this study comprises all companies listed in the SRI KEHATI index from 2019 to 2022. The sampling method employed in this research is purposive sampling, with a total of 64 samples used. The data utilized in this study are obtained from the Bloomberg database, annual reports, and financial statements. The data are analyzed using multiple regression techniques, preceded by classical assumption tests. The findings of this study indicate that environmental disclosure does not affect firm value. However, social and governance disclosures have a positive impact on firm value. Additionally, the dividend policy negatively influences firm value.